"Pretends to be free" : runaway slave advertisements from Colonial and Revolutionary New York and New Jersey - Hodges, Graham Russell, 1946-; Brown, Alan Edward (Fordham University Press, 2019)
Republication on the twenty-fifth anniversary of "Pretends to Be Free" recognizes the signal importance of its sterling presentation of northern self-emancipation. Today, even more than a quarter-century ago, these fugitive slave notices are the best verbal snapshots of enslaved Americans before and during the American Revolution. Through these notices, readers can discover how enslaved blacks chose allegiance during our War for Independence. Replete with a preface by Edward E. Baptist, the leading scholar of slavery and capitalism and director of a massive project aimed at digitalizing every escape notice, and with a new Introduction and teacher's guide by Graham Hodges, this new edition makes this documentary study more relevant than ever.